2007
DOI: 10.3818/jrp.9.2.2007.31
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Place, and Perpetrators: Using NIBRS to Explain Arrest Practices in Intimate Partner Violence

Abstract: This study presents the results of a multilevel analysis of arrest outcomes in intimate partner incidents reported to the police. Using NIBRS data for 2000 in combination with data from other sources, we investigate how arrest policies, levels of urbanization, incident circumstances and offender characteristics influence arrest outcomes in domestic violence incidents. Our results indicate that arrest outcomes for intimate partner violence are influenced not only by mandatory arrest legislation, but also by lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
2
38
1
Order By: Relevance
“…The dependent variable for the analysis is the monthly count of incidents of family violence reported to the police, compiled in the National Incident-Based Reporting Program (NIBRS) for Massachusetts cities and towns. NIBRS data have been used in a number of studies that examine the context and consequences of intimate partner violence (Hirschel, Buzawa, Pattavina, & Faggiani, 2007; Pattavina, Buzawa, Hirschel, & Faggiani, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable for the analysis is the monthly count of incidents of family violence reported to the police, compiled in the National Incident-Based Reporting Program (NIBRS) for Massachusetts cities and towns. NIBRS data have been used in a number of studies that examine the context and consequences of intimate partner violence (Hirschel, Buzawa, Pattavina, & Faggiani, 2007; Pattavina, Buzawa, Hirschel, & Faggiani, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…child to parent) violence to other acquaintance violence. Their results also showed that intimate partner violence was more likely to lead to arrest in rural than in urban jurisdictions, debunking the common view that domestic violence arrests are not a priority in rural areas (Pattavina, Buzawa et al. 2007).…”
Section: Crime Clearance Researchmentioning
confidence: 91%
“…2004), the interaction between the racial composition of a city's police force and the offender's race in assault clearance (Eitle et al. 2005), and the effects of state law and agency‐level policies on individual officers’ arrest behavior in domestic violence incidents (Eitle 2005; Pattavina, Buzawa et al. 2007; Pattavina, Hirschel et al.…”
Section: Crime Clearance Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A host of researchers have made use of NIBRS arrest data to study aspects of intimate partner violence. Multiple studies have investigated the police decision to make an arrest in intimate partner violence cases (Dichter, Marcus, Morabito, & Rhodes, 2011; Durfee & Fetzer, 2016; Hirschel & Buzawa, 2013; Pattavina, Buzawa, Hirschel, & Faggiani, 2007). Likewise, research has studied the correlates of arrests for domestic violence offenses (Durfee, 2012; Eitle, Stolzenberg, & D’Alessio, 2005; Hirschel, Hutchison, & Shaw, 2010; Hirschel & Hutchison, 2011; Strom, Warner, Tichavsky, & Zahn, 2014; Vazquez, Stohr, & Purkiss, 2005).…”
Section: Introductionmentioning
confidence: 99%